Demographic, Clinical, and Laboratory Characteristics of HIV Patients with Cerebral Toxoplasmosis at Haji Adam Malik General Hospital Medan - Alfansuri Kadri; Eko Yandra (Fakultas Kedokteran Universitas Brawijaya, 2022)
Cerebral toxoplasmosis is one of the frequent opportunistic infections of the central nervous system of Human Immunodeficiency Virus (HIV) patients in the presence of Toxoplasma Gondii infection. In Indonesia, the incidence of HIV patients with cerebral toxoplasmosis is 45%. This study was done to determine the demographic, clinical, and laboratory characteristics of HIV patients with cerebral toxoplasmosis at Haji Adam Malik Hospital, Medan, based on medical record data in 2022. The total sample was 23 patients with time periods from January to March 2022. Demographically, the data showed that most of the HIV patients with cerebral toxoplasmosis were male (91.3%), a mean age of 36.48 ± 5.74 years, married (87%), high school graduates (69.6%), and working (91.3%). The most common clinical characteristics were headache (69.6%) and cognitive impairment (56.5%). Laboratory characteristics found were (56.5%) non-reactive (<0.8 COI) and (43.5%) reactive (≥1 COI) anti toxoplasma IgM, while reactive anti-toxoplasma IgG (≥3 IU/ml) was obtained in all research samples (100%).